Cellulose nanocrystal-reinforced keratin bioadsorbent for effective removal of dyes from aqueous solution. (May 2017) - Song, Kaili; Xu, Helan; Xu, Lan; Xie, Kongliang; Yang, Yiqi
Graphical abstract: Highlights: CNC reinforced keratin bioadsorbent was developed for dye removal. The adsorption capacities for RB5 and DR80 were 1201 and 1070 mg g −1, respectively. The bioadsorbent could be regenerated easily and simply. The bioadsorbent displayed excellent regeneration and recyclability. Fixed bed column studies verified excellent performance of the bioadsorbent. Abstract: High-efficiency and recyclable three-dimensional bioadsorbents were prepared by incorporating cellulose nanocrystal (CNC) as reinforcements in keratin sponge matrix to remove dyes from aqueous solution. Adsorption performance of dyes by CNC-reinforced keratin bioadsorbent was improved significantly as a result of adding CNC as filler. Batch adsorption results showed that the adsorption capacities for Reactive Black 5 and Direct Red 80 by the bioadsorbent were 1201 and 1070 mg g −1, respectively. The isotherms and kinetics for adsorption of both dyes on bioadsorbent followed the Langmuir isotherm model and pseudo-second order model, respectively. Desorption and regeneration experiments showed that the removal efficiencies of the bioadsorbent for both dyes could remain above 80% at the fifth recycling cycles. Moreover, the bioadsorbent possessed excellent packed-bed column operation performance. Those results suggested that the adsorbent could be considered as a high-performance and promising candidate for dye wastewater treatment.